Analisis Pushover terhadap Kinerja Seismik Gedung Beton Bertulang dengan Variasi Konfigurasi Dinding Geser - Pradnya Paramitha Pinasthika; Dr. Ir. Retno Anggraini, ST., MT.; Dr. Eng. Achfas Zacoeb, ST., MT. (Jurnal Mahasiswa Jurusan Teknik Sipil, 2026)
Indonesia is a region with high seismic activity due to its location on the Pacific Ring of Fire, making earthquake-resistant building design a highly crucial aspect. This study aims to evaluate the effect of adding shear walls on the seismic performance of Building X at University Y in Malang City. The case study building is a 7-story reinforced concrete structure with a height of 30.1 meters, which initially utilized a moment-resisting frame system. The methodology involves a nonlinear static pushover analysis utilizing ETABS software. The analysis was conducted on four structural variations: Type 1 (without shear walls), alongside Types 2, 3, and 4 (incorporating various shear wall configurations). Structural performance levels were evaluated based on SNI 1726:2019 and ATC-40 standards using the capacity spectrum method. The findings reveal that the integration of shear walls significantly enhances both the stiffness and lateral capacity of the building. In the original state (Type 1), the structure remained at the Damage Control (DC) performance level, recording a peak displacement of 240.216 mm in the X-direction and 218.834 mm in the Y-direction. Conversely, Type 3 and Type 4 successfully elevated the structural performance to the Immediate Occupancy (IO) level. Type 3 emerged as the most optimal configuration, yielding the smallest displacement in the X-direction (33.454 mm) and demonstrating a substantial increase in base shear compared to the unbraced structure. Consequently, the shear wall configuration in Type 3 is highly recommended, as it effectively meets the target safety performance while offering greater material efficiency. Keywords: Pushover Analysis, Shear Wall, Seismic Performance, ATC-40, ETABS